Pengaruh Media Powerpoint Interaktif Terhadap Hasil Belajar Siswa pada Pembelajan IPAS Siswa Kelas V SDN 06 Sungai Raya - Gunawan, Windra (Indo-MathEdu Intellectuals Journal, 2025)
Interactive PowerPoint is useful as a learning platform that utilizes interactive elements to increase student engagement in the learning process. The purpose of this study is to determine the effect of the use of interactive PowerPoint media on the learning outcomes of grade V students of SDN 06 Sungai Raya.This study uses a quantitative method with a nonequivalent control group design. The results of the independent t-test showed that the use of Interactive PowerPoint media had a significant effect on student learning outcomes in social studies learning with a significance value of 0.001. From these results, the conclusion is that H0 is rejected because of the significance value of sig. (2-tailed) is significantly smaller than 0.05. The average post-test score of the experimental class was 89.77 higher than the average post-test of the control class of 61.41. It should be noted that the use of interactive PowerPoint media affects the learning outcomes of social studies students in grade V of SDN 06 Sungai Raya. The results of the analysis showed that the use of interactive powerpoints had an effect on the learning outcomes of grade V students at SD Negeri 6 Sungai Raya. The increase in social science learning outcomes before and after using interactive powerpoint in students, with the average posttest score higher than the pretest score.